Immunity and Mental Health: Towards COVID-19 - Malhotra, Varun; Bharshankar, Rajay; Mukherjee, Sukesh; Gupta, Akriti; Gautam, Namita (Janaki Medical College Journal of Medical Science, 2020)
Introduction: The Corona virus that originated in China in December 2019, has now spread rapidly globally. It is highly contagious & to date no cure in form of vaccine or medicines is available. COVID-19 and Immunity: Enhancing body’s natural defense system plays an important role in maintaining optimum health. The serum levels of IL2R and IL-6 in patients with COVID-19 are positively correlated with the severity of the disease . studies have found that, compared with COVID-19 patients from general wards, patients in the intensive care unit [ICU] display increased serum levels of granulocyte colony-stimulating factor, IP-10, MCP-1, macrophage inflammatory protein-1A, and TNF-α. COVID-19 and Mental Health: Patients who had positive COVID-19 diagnosis reported significantly elevated levels of corona virus anxiety compared to their non-infected, but anxious peers, this highlights the clinical utility of the Corona Anxiety Scores [CAS]&the importance of assessing, treating the psychological needs of those infected with the virus. The need to formulate psychological interventions to improve mental health and psychological resilience during COVID-19 pandemic is the need of the hour. We need to tackle and fight the stigma, fear &anxiety related to the virus that is greater than the disease itself. Governments have provided mental health services to their citizens by varied channel including hotline, online consultation & course and outpatient consultation, but have indicated that more attention should be paid to depression and anxiety. As India’s cases increase, the importance of following the government laid precautions becomes all the more important.